Enhanced Visible Light Photocatalytic Activity of Mesoporous Anatase TiO2 Codoped with Nitrogen and Chlorine. (20th February 2012) - Cheng, Xiuwen; Yu, Xiujuan; Xing, Zipeng; Yang, Lisha
Abstract : Anatase mesoporous titanium dioxide codoped with nitrogen and chlorine (N-Cl-TiO2 ) photocatalysts were synthesized through simple one-step sol-gel reactions in the presence of ammonium chloride. The resulting materials were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), and ultraviolet-visible diffuse reflection spectrum (UV-vis DRS). XRD results indicated that codoping with nitrogen and chlorine could effectively retard the phase transformation of TiO2 from anatase to rutile and the growth of the crystallite sizes. XPS revealed that nitrogen and chlorine elements were incorporated into the lattice of TiO2 through substituting the lattice oxygen atoms. DRS exhibited that the light absorption of N-Cl-TiO2 in visible region was greatly improved. As a result, the band gap of TiO2 was reduced to 2.12 eV. The photocatalytic activity of the as-synthesized TiO2 was evaluated for the degradation of RhB and phenol under visible light irradiation. It was found that N-Cl-TiO2 catalyst exhibited higher visible light photocatalytic activity than that of P25 TiO2 and N-TiO2, which was attributed to the small crystallite size, intense light absorption in visible region, and narrow band gap.